Research for the industrialization of a natural drink from the Andean tumbo (Passiflora mollissima) with linseed (Linum usitatissimum) - Córdova-Lavado, Isaac César (2016)
This article presents the results of a research for the development of a natural drink made from an exotic fruit (tumbo) with linseed, in order to offer a new, healthy and natural product for easy to consume. The product is accepted in men and women aged 18 to 60 who belong to segments A and B of Lima and will be marketed in glass containers 300 ml; also it states that the project is economically and fi nancially viable.